Influence of intrinsic spin in the formation of singularities for inhomogeneous effective dust space-times - Luz, Paulo (2019)
The evolution of inhomogeneous space-times composed of uncharged fermions is studied for Szekeres metrics which have no Killing vectors, in general. Using the Einstein-Cartan theory to include the effects of (intrinsic) matter spin in general relativity, the dynamics of a perfect fluid with nonnull spin degrees of freedom is considered. It is shown that, if the matter is composed by effective dust and certain constraints on the initial data are verified, a singularity will not form. Various special cases are discussed, such as Lemaitre-Tolman-Bondi and Bianchi I space-times, where the results are further extended or shown explicitly to be verified.